AI-POWERED SHOPPING: RESHAPING ONLINE RETAIL IN INDIA - Michael , David Johnson; Emily , Elizabeth Brown (Ayden Journal of Management and Social Sciences, 2024)
Artificial intelligence (AI), characterized by its ability to emulate cognitive functions akin to the human mind, has emerged as a transformative force across various sectors. As outlined in "Artificial Intelligence: A Modern Approach (AIMA)" by Russell and Norvig (2020), AI encompasses technologies that facilitate learning and problem-solving, revolutionizing the way tasks are performed by machines. In India, the adoption of AI has witnessed exponential growth, with industries increasingly investing in research and development in this domain. A study conducted by PricewaterhouseCoopers (PwC) India in 2020 revealed a remarkable surge in AI utilization amidst the global pandemic, with India registering the highest increase in AI usage at 45%, surpassing developed nations such as the US, UK, and Japan. This surge underscores the growing recognition of AI's potential to drive innovation, enhance efficiency, and address complex challenges across various sectors in India. This abstract delves into the burgeoning presence of AI in India, tracing its evolution and highlighting its profound impact on industries and society. Drawing on insights from Russell and Norvig (2020) and PwC India, the abstract sheds light on the accelerating pace of AI adoption in response to emerging global trends and challenges. Understanding the dynamics of AI adoption in India is crucial for policymakers, businesses, and stakeholders seeking to harness the transformative potential of AI to foster economic growth, innovation, and societal well-being.